2019
DOI: 10.1042/bcj20190507
|View full text |Cite
|
Sign up to set email alerts
|

Cycloserine enantiomers are reversible inhibitors of human alanine:glyoxylate aminotransferase: implications for Primary Hyperoxaluria type 1

Abstract: Peroxisomal alanine:glyoxylate aminotransferase (AGT) is responsible for glyoxylate detoxification in human liver and utilizes pyridoxal 5′-phosphate (PLP) as coenzyme. The deficit of AGT leads to Primary Hyperoxaluria Type I (PH1), a rare disease characterized by calcium oxalate stones deposition in the urinary tract as a consequence of glyoxylate accumulation. Most missense mutations cause AGT misfolding, as in the case of the G41R, which induces aggregation and proteolytic degradation. We have investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…While several crystal structures of AGT‐Ma were solved, 24–30 no structural information on AGT‐Mi was available. Therefore, we first solved the structure of AGT‐Mi by x‐ray crystallography at 2.2 Å resolution (Figure 1, Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While several crystal structures of AGT‐Ma were solved, 24–30 no structural information on AGT‐Mi was available. Therefore, we first solved the structure of AGT‐Mi by x‐ray crystallography at 2.2 Å resolution (Figure 1, Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure of AGT-Mi unveils three unexpected frustrated regions and allows to decipher AGT1 hidden plasticity While several crystal structures of AGT-Ma were solved, [24][25][26][27][28][29][30] no structural information on AGT-Mi was available. Therefore, we first solved the structure of AGT-Mi by x-ray crystallography at 2.2 Å resolution (Figure 1, Table S1).…”
mentioning
confidence: 99%
“…Molecular docking has been performed using the MOE Dock Tool available on MOE 2018.0101(Chemical Computing Group ULC, Montreal, QC, Canada) as previously reported. 53 Briefly, the crystal structure of human AGT (PDB ID:1H0C) 1 and the ligand (compound 1) have been prepared and protonated using the Protonated 3D Tool and the docking site selected by using the MOE Site Finder Tool. Then, a collection of ligand conformations using the bond rotation method has been generated, placed in the selected site by the Triangle Matcher method, and ranked using the London dG scoring function, which estimates the free energy of binding of the ligand from a given pose.…”
Section: ■ Materialsmentioning
confidence: 99%
“…Interestingly, only D-cycloserine displays a PC activity on a mutant form of AGT prone to misfolding. The latter data have suggested that a new line of intervention against PH1 could be also based on a drug repositioning approach [174].…”
Section: Primary Hyperoxaluria Type Imentioning
confidence: 99%